Replacing maize grain with self-fermented agro-waste in total mixed ration improves fatty acid profile, oxidative stability and meat quality traits in goats - Rajat Bagdas; Gauri Jairath; Varun; Suman Bishnoi; Yashavanth Basavapatna Subbanna; Gorakh Mal; Ashim K. Biswas; Triveni Dutt; Arup Ratan Sen; Randhir Singh Bhatt; Lalit Kumar Soni; Birbal Singh; et al. (Meat Science, 2026)

A theoretical evaluation of cyclostrophic balance in the Venusian atmosphere using the Venus Planetary Climate Model - Jayadev Pradeep; S.V. Sunilkumar; N. Koushik; Varun Nikam; K.R. Lakshmi; S. Sijikumar; K. Kishore Kumar; Govindan Kutty (Icarus, 2026)

Green synthesis of biomass derived zinc-ferrite bimetallic nanoparticles and their catalytic applications to access bioactive nitrogenous heterocyclic scaffolds - Ekta Bala; Ankit Kachore; Varun Aggarwal; Hemant Singh; Ishika Sharma; Himanshu; Rohit Sharma; Saima; Rakesh Kumar; Kasim Sakran Abass; Praveen Kumar Verma (Journal of Environmental Chemical Engineering, 2026)

Highly dispersed Cu on TiO₂ for photoreduction of hexavalent chromium in the presence of glycerol - Srishti; Shweta Kumari; Sumit Kumar Pathak; Abhishikta Chatterjee; Varun Kumar Gupta; Aditya Kumar; Apurba Sinhamahapatra (Journal of Environmental Chemical Engineering, 2026)

Acitretin shows promising potential in Alzheimer’s disease: retinoid-driven modulation of amyloid processing, neuroinflammation, and translational prospects - Varun Sharma; Kanika Vashisht; Garima Choudhary; Vaishali Choudhay; Vandana Bhatia; Mahendra Singh Ashawat; Ashish Baldi; Shiv Kumar Kushawaha (Inflammopharmacology, 2026)

An analytical model for subsurface ground motions due to kinematic shear dislocation sources in layered media - Jahnabi Basu; B Shree Rashmi; S.T.G. Raghukanth; Varun Kumar Singla (Soil Dynamics and Earthquake Engineering, 2026)

Real-time traffic congestion detection using smartphone multi-sensor data and stacked ensemble learning - Ritesh Kumar; Varun Singh; Shahrukh (Innovative Infrastructure Solutions, 2026)

Predictive modelling of soil organic carbon, carbon stocks, and fractions across elevation gradients in the dry-temperate region of North-West Himalaya - Varun Parmar; Rushali Katoch; Naveen Datt; Pardeep Kumar; Ranbir Singh Rana; Narender Kumar Sankhyan; Rishi Mahajan; Justin George Kalambukattu (Environmental Monitoring and Assessment, 2026)

Supplementation with minerals and multi-strain probiotics attenuate neonatal piglet mortality, improve growth rate and augment systemic and mucosal immune parameters - Sakshi; Ujjwal Kumar De; Anju Kala; Varun Kumar Sarkar; Amit Kumar; Anuj Chauhan; Narayana Rathode (Veterinary Immunology and Immunopathology, 2026)

A new paradigm in Parkinson’s disease: kidney-origin α-synuclein pathology driven by PKC signaling and aurothioglucose - Kanika Vashisht; Varun Sharma; Mahendra Singh Ashawat; Ashish Baldi; Shiv Kumar Kushawaha (Inflammopharmacology, 2026)

From glycemic control to neuroprotection: alogliptin as a repurposed candidate for Huntington’s disease - Garima Choudhary; Kanika Vashisht; Varun Sharma; Mahendra Singh Ashawat; Shiv Kumar Kushawaha (Metabolic Brain Disease, 2026)

Repurposing apremilast for alzheimer’s disease: multitarget modulation of cAMP‑PI3K/Akt–GSK‑3β and NF‑κB signaling - Nitish Choudhary; Shakshi Rana; Kanika Vashisht; Varun Sharma; Vandana Bhatia; Mahendra Singh Ashawat; Shiv Kumar Kushawaha (Metabolic Brain Disease, 2026)

Updated Recommendations for the Bioanalysis of Antibody–Drug Conjugates (ADC) from the ADC working group of the AAPS Bioanalytical Community - Jim X. Shen; Robert Dodge; Shoshana Oberstein; Jennifer Cunliffe; Varun Ramani; Soumya Mohana Sundaram; Ines C. Santos; Chongwoo Yu; Sanjay L. Dholakiya; Seema Kumar; Xiaohui Sophia Xu; Sasha Fraser; et al. (The AAPS Journal, 2026)
Antibody–drug conjugates (ADCs) represent a rapidly evolving therapeutic modality, combining the selective targeting of monoclonal antibodies with highly potent small molecule payloads. Their inherent structural complexity demands a sophisticated and multi-faceted bioanalytical approach spanning preclinical discovery through late-stage clinical development. This white paper, developed by the ADC Working Group of the AAPS bioanalytical community, comprising over 100 members from industry, contract research organizations (CROs), and regulatory agencies, provides updated recommendations for ADC bioanalysis. Building upon the foundational 2013 AAPS position paper and recent publications governing regulatory frameworks on PK considerations, this work addresses advances in bioanalytical quantitation strategies for total antibody (tAb), conjugated ADC, free (unconjugated) payload, and drug-to antibody ratio (DAR); novel immunogenicity assessment considerations; soluble target interference; critical reagent lifecycle management; payload-specific stability requirements; cross-validation strategies; and regulatory considerations. The recommendations presented herein reflect over a decade of scientific progress and are designed to serve as a comprehensive, empirically validated, and industry aligned bioanalytical framework for contemporary ADC drug development.

Optimizing and understanding complex relationships between micro-inertia and spin gradient viscosity in off-centered stagnation point flow - Vishwanatha R. Banakar; K. Karthik; Shakti Prakash Jena; R.S. Varun Kumar (Dynamics of Atmospheres and Oceans, 2026)

Design and Development of Myco-Mediated Bioremediation System for the Treatment of Runoff and Grey Water - Anupam Barh; Uday Mandal; J. M. S. Tomar; Deepak Singh; Varun Chauhan; Sudheer Kumar Annepu; Rama Pal; M. Muruganandam; Trisha Roy; A. C. Rathore; A. K. Gupta; Devideen Yadav; et al. (Water, Air, & Soil Pollution, 2026)

Exploring the application of various condenser microphones for wrist pulse measurement using machine learning models - Chetna Sharma; Neha; Gurinderjit Singh; Yogesh Kumar; Varun Dhiman; Sanjeev Kumar (Physical and Engineering Sciences in Medicine, 2026)

Spatial analysis and hybrid machine learning prediction of forest fire susceptibility: a longitudinal appraisal synergy with physiographic division - Netrananda Sahu; Pritiranjan Das; Prince Gupta; Suraj Kumar Mallick; Rajiv Pandey; Xiaojun Wang; Manish Kumar; Ayush Varun; Ravi Kesharwani; Anil Kumar (Advances in Space Research, 2026)

The Impact of Earthquake Swarms Occurred in the South Scotia Sea over Antarctica and South America - A. Akilan; H. Schuh; C. Varun; G. G. Krishna Teja; Sravan Kumar Kotluri; T. T. Charan; M. Satyanarayanan; H. V. S. Satyanarayana (Pure and Applied Geophysics, 2026)

Therapeutic milestones against multidrug resistant Acinetobacter baumannii: from legacy antibiotics to Zosurabalpin - Jaya Malik; Shilpy Singh; Dharmsheel Shrivastav; Ved Vrat Verma; Ravi Kant Pal; Manoj Kumar Mishra; Varun Kumar Sharma (Archives of Microbiology, 2026)

Climate change impacts on vegetation dynamics and transhumant pastoralism in the Western Himalayas - Netrananda Sahu; Ravi Kesharwani; Yogeshwar Singh Rathore; Anil Kumar; Ayush Varun; Martand Mani Mishra; Pritiranjan Das; Basanta K. Das; Suraj Kumar Mallick (Environmental Monitoring and Assessment, 2026)

A deep learning mobile application for tomato leaf nutrition deficiency identification with YOLOv8 and enhanced augmentation - Kamaldeep Joshi; Varun Kumar; Sumit Kumar; Kriti Katyal; Rainu Nandal; Ashima Nehra; Kashmir Singh; Narendra Tuteja; Ritu Gill; Sarvajeet Singh Gill (Plant Science, 2026)

Effect of strategic supplementations of antioxidant multiminerals and vitamins to transitional buffaloes on serum biochemistry, non-esterified fatty acid and calf health - Desh Deepak; Ujjwal Kumar De; Tarun Kumar Sarkar; Gulab Chandra; Varun Kumar Sarkar (Tropical Animal Health and Production, 2026)

ANN-based broadband modelling of Fourier amplitude spectra through physics-based simulations: application to 2023 Elbistan earthquake - Varun Sharma; J. Dhanya; Maheshreddy Gade; Harsh Kumar Arya (Journal of Seismology, 2026)

Comprehensive genomic analysis of rabies virus in India reveals distinct lineages and evolutionary stability - Chakrakodi N. Varun; Shubhangi Chandel; Dhanya Keshava Kumar; Nayana Siddalingaiah; Surbhi Telang; Preeti Soundarya Bhalke; Shrikrishna Isloor; Vijaylakshmi Reddy; M. A. Ashwini; Anita Mahadevan; Reeta S. Mani (Virus Genes, 2026)

MRO-MCS observed cold spots during the Martian year 34 global dust storm - Anirban Mandal; Jagabandhu Panda; Nirvan Abhilash; Bijay Kumar Guha; Varun Sheel (Icarus, 2026)

Toxicity of Semaglutide upon sub chronic administration in Rabbits - Chandrashekara Vishwanath; Kumar Krishnachari; Gowrav Perdur Adiga; Manohar Madhavdeshmukh; Akanksh Das; Zabiullah Alandur Jamal; Prabhakar Bhoite; Kalaiselvan Ponnusamy; Mohan Krishnappa; Varun Ahuja; Manoj Kumar Pananchukunnath; Anil Kunhihitlu; et al. (Toxicological Research, 2026)

Boundary Layer Meteorology in Elysium Planitia, Mars During a Global Dust Storm - Insights from a Dust Reservoir - Varun Sheel; Rishitosh Kumar Sinha; Tirtha Jyoti Kalita (Journal of the Indian Society of Remote Sensing, 2026)

Effect of Monochromatic Light Spectra on Morphophysiological and Biochemical Properties of Chrysanthemum morifolium cv. Zembla Under Different Temperature Regimes - Panchal Sangmesh; Mam Chand Singh; Lekshmy Sathee; Gunjeet Kumar; Namita; Amrender Kumar; Ediga Amala; B. H. Varun; Neeraj Singh Negi (Journal of Plant Growth Regulation, 2025)

Phytochemical analysis and toxicity evaluation of Uraria picta (Jacq.) Desv. ex DC. through In Vitro and In Vivo approaches - Richa Yadav; Varun Gorki; Shabnam Thakur; Shubhangi Kansal; Sofia Gupta; Birendra Kumar; Upninder Kaur; Bikash Medhi; Rakesh Sehgal (Next Research, 2025)

Insights into Pinus species: phytochemistry, pharmacology and industrial potential of Indian Pinus species - Rohit Sharma; Rahul Sharma; Varun Thakur; Aditi Randhawa; Rajneesh Kumar; Bhupender Dutt; Ashun Chaudhary; Sunil Kumar (Phytochemistry Reviews, 2025)

Emerging contaminants in healthcare effluents: antibiotic resistance and virulence factor dissemination - Jaya Malik; Zayera Naushad; Shilpy Singh; Dharmsheel Shrivastav; Ved Vrat Verma; Manoj Kumar Mishra; Ravi Kant Pal; Varun Kumar Sharma (Folia Microbiologica, 2025)

The environmental threat of macrolide resistance: mechanisms, dissemination pathways, and urgent mitigation strategies - Arpana Devi; Varun Kumar Sharma; Dharmsheel Shrivastav; Shilpy Singh (Environmental Monitoring and Assessment, 2025)

Multi-hazard microzonation of Joshimath, India, considering seismic and landslide hazards - Varun Kumar; Vibhav Kumar Gupta; Rajib Sarkar; Sanjit Kumar Pal (Journal of Earth System Science, 2025)

Exploring the Therapeutic Landscape of Probiotics in Enteric and Respiratory Viral Infections - Yashpal Singh Malik; Aakriti Pathania; Ujjwal Kumar De; Manu M.; Harsh Panwar; Jaspreet Kaur; Adarsh Mishra; Naveen Kumar; Souvik Ghosh; Varun Kumar Sarkar; Sakshi (Probiotics and Antimicrobial Proteins, 2025)

An investigative assessment of the stability of natural and road-cut rock slopes using empirical rock mass classification systems and numerical methods: case study of NH-07 from the Garhwal Himalayas, India - Nalini Das; Subhamoy Ghosh; Rajendra Kumar Rawat; Barun Bedanta Sahoo; Varun Shastri; Sumana Murmu (Natural Hazards, 2025)

Utility of Urinary Biomarkers for Diagnosis of Acute Kidney Injury (AKI) in COVID-19 - Tanvir Samra; Vinod Kumar; Raja Ramachandran; Varun Mahajan; Naveen B. Naik; Goverdhan Dutt Puri; Ashish Bhalla; Arnab Pal; Ravi Dixit; Prabhjot Kaur (Indian Journal of Clinical Biochemistry, 2025)

Altitude-driven changes in carbon storage, soil properties, and leaf nutritional value of Quercus semecarpifolia in the northwestern Himalayas - Rishav Sharma; Rohit Bishist; Rajesh Kaushal; Prem Prakash; Krishan Lal Gautam; Ashok Kumar; Harish Sharma; Varun Thakur; Munesh Kumar (Environmental Sustainability, 2025)

Integrated optical and SAR data analysis for the monsoonal flood hazard mapping in the Tawi Basin Northwest Himalaya - Ajay Kumar Taloor; Varun Khajuria; Savati Sharma; Gurnam Parsad; Shiwalika Sambyal; Girish Ch Kothyari; Meenakshi Sharma; Pankaj Mehta (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Relationship between gut microbiota and multiple sclerosis: A comprehensive bibliometric and visual analysis of global research trends and therapeutics - Anupam Bhattacharya; Kushagra Agarwal; Nirmal Kumar Ganguly; Varun Suroliya (Next Research, 2025)

Carbon dots: An emerging food analysis nanoprobes for detection of contaminants - Hemant Singh; Saima; Varun Aggarwal; Ankit Kachore; Ekta Bala; Rakesh Kumar; Rohit K. Sharma; Praveen Kumar Verma (Food Chemistry, 2025)

Druggability assessments of small peptides as protein–protein interaction inhibitors targeting EED-EZH2 binding within the Polycomb Repressive Complex 2 (PRC2), an epigenetic regulator - Varun Thachan Kundil; Sharanya C. Suresh; Sreeja Chellappan; Anupama Kizhakkepurayil; Soorej Muhammad Basheer; Arun Kumar Gangadharan (Molecular Diversity, 2025)

An Updated Perspective on Skin Disease Therapy: From Conventional Methods to Nanocarrier Innovations - Riya Shivgotra; Bindu Soni; Parminder Kaur; Anshuka Sharma; Varun Singh; Nitin Partap; Hossamaldeen Bakrey; Subheet Kumar Jain (AAPS PharmSciTech, 2025)

Unravelling sustainable impediments in E-waste supply chain management: A Fuzzy-WINGS decision approach - Varun Kumar; Om Ji Shukla (Journal of Environmental Management, 2025)

Data-driven techniques in rainfall forecasting using CMIP6 simulation outputs and ground-observed data - Varun Dubey; Vikas Kumar Vidyarthi (Acta Geophysica, 2025)

Land use change analysis and prediction of urban growth using multi-layer perceptron neural network Markov chain model in Faridabad- A data-scarce region of Northwestern India - Sunil Kumar; Kousik Midya; Swagata Ghosh; Pradeep Kumar; Varun Narayan Mishra (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Spatio-temporal Variations and Forecast of PM2.5 concentration around selected Satellite Cities of Delhi, India using ARIMA model - Vipasha Sharma; Swagata Ghosh; Varun Narayan Mishra; Pradeep Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Ground shaking hazard assessment in Jharkhand state, India, using deterministic approach - Varun Kumar (Acta Geophysica, 2025)

Characterization of azo dye-degrading Tistrella mobilis isolated from industrial effluents: a molecular perspective - Ufondu Maryann Afoma; Jaya Malik; Shilpy Singh; Abhishek Kumar Mishra; Lomas Kumar Tomar; Aditi Tomar; Ved Vrat Verma; Manoj Kumar Mishra; Varun Kumar Sharma (Biologia, 2025)

Assessing Gaddi dogs as a non-lethal predator deterrent in the north-western Himalayan transhumant pastoralism - Ankaj Thakur; Rakesh Thakur; Aadarsh Kumar; Brij Vanita; Varun Sankhyan; Shivani Katoch (Journal of Veterinary Behavior, 2025)

Seasonal patterns of air pollution in Delhi: interplay between meteorological conditions and emission sources - Najib Ansari; Preeti Kumari; Rahul Kumar; Pavan Kumar; Aquib Shamshad; Saddam Hossain; Ashutosh Sharma; Yogeshwar Singh; Maya Kumari; Varun Narayan Mishra; Rukhsana; Akram Javed (Environmental Geochemistry and Health, 2025)

Influences of anaerobic treatment on chemical oxygen demand removal behavior of tannery wastewater - Venkatesh Rathinavelu; Viyat Varun Upadhyay; Rakesh Kumar; Vinayagam Mohanavel; Nagabhooshanam Nagarajan; Dhaval Rabadiya; Manzoore Elahi Mohammed Soudagar; Sami Al Obaid; Saleh Hussein Salmen (Environmental Monitoring and Assessment, 2025)

Spatiotemporal dynamics of rice cultivation in India - Netrananda Sahu; Ravi Kesharwani; Pritiranjan Das; Anil Kumar; Ayush Varun; Atul Saini; Suraj Kumar Mallick; Martand Mani Mishra (Tropical Ecology, 2025)

ANN-Based Ground Motion and Physics-Based Broadband Models for Vertical Spectra - Varun Sharma; Harsh Kumar Arya Author; Maheshreddy Gade; J. Dhanya (Pure and Applied Geophysics, 2025)

Influence of Bemisia tabaci-Induced Plant Volatiles on the Host-Choice Behavior of Tuta absoluta - Subhash Shivaramu; Kamala Jayanthi Pagadala Damodaram; Anuj Bhatnagar; Kailash Chandra Naga; Varun Yennurukadirenahalli Byregowda; Aarti Bairwa; Sanjeev Sharma; Rajesh Kumar Singh; Brajesh Singh; Vivek Kempraj (Journal of Chemical Ecology, 2025)

Novel extraction technique: quantification of major phytoconstituents of arjuna in infused edible oil - Rajesh Kumar Verma; Neelam Pal; Sujeet Gupta; Varun Kumar Singh; Priyanka Gupta; Sunanda Handoo; Charan Singh Rana (Natural Product Research, 2025)

Seismic hazard assessment of Faizabad region of Uttar Pradesh, India, utilizing deterministic and probabilistic approaches - Varun Kumar; Prosanta Kumar Khan; Rajib Sarkar; Sanjit Kumar Pal (Journal of Earth System Science, 2024)

Spatially explicit simulation and forecasting of urban growth using weights of evidence based cellular automata model in a millennium city of India - Pankaj Kumar Yadav; Varun Narayan Mishra; Maya Kumari; Akshay Kumar; Pradeep Kumar; Rajeev Bhatla (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Single-cell transcriptomics: a new frontier in plant biotechnology research - Shilpy Singh; Afsana Praveen; Namrata Dudha; Varun Kumar Sharma; Pooja Bhadrecha (Plant Cell Reports, 2024)

A state-of-art review on photovoltaic systems: Design, performance, and progress - Abhishek Saxena; Rajneesh Kumar; Atul A. Sagade; Desh Bandhu Singh; V.V. Tyagi; Erdem Cuce; Varun Goel (Process Safety and Environmental Protection, 2024)

Unveiling pollutants in Sonipat district, Haryana: Exploring seasonal, spatial and meteorological patterns - Diksha; Maya Kumari; Varun Narayan Mishra; Deepak Kumar; Pradeep Kumar; Hazem Ghassan Abdo (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Environmental Magnetic and Morphological Characteristics of Topsoils from the Coal Capital of India-Dhanbad - Mahesh Kapawar; Varun Kumar; Ravi Shankar; Venkateshwarlu Mamilla (Water, Air, & Soil Pollution, 2024)

Synthesis, characterization, and study of photocatalytic degradation of aniline blue dye using copper oxide nanoparticles prepared by Santa Maria feverfew leaf extract - Upendra Kumar Mishra; Vishal Singh Chandel; Avaneesh Kumar Yadav; Abhishek Kumar Gautam; Aditya Dev Anand; Juli Varun; Amit Kumar Rai; Satyendra Pratap Singh (Nanotechnology for Environmental Engineering, 2024)

Clinical and Genomic Perspective of SARS CoV-2 Infection in Liver Disease Patients: A Single-Centre Retrospective Study - Reshu Agarwal; Arjun Bhugra; Pramod Gautam; Varun Suroliya; Ruchita Chhabra; Amit Pandey; Prince Garg; Pooja Rao; Rosmy Babu; Guresh Kumar; Chhagan Bihari; Debajyoti Bhattacharyya; et al. (Current Microbiology, 2024)

Five Himalayan weeds as potential bioresources for bioactive agents: toxic compounds to valuable scaffolds - Ekta Bala; Varun Aggarwal; Pawan Kumar; Rohit Sharma; Saima; Manickam Selvaraj; Mohammed A. Assiri; Praveen Kumar Verma (Phytochemistry Reviews, 2024)

Impact of urban growth in Delhi and It's Peri-urban environment on urban heat exposure - Suraj Kumar Mallick; Netrananda Sahu; Pritiranjan Das; Biswajit Maity; Ayush Varun; Anil Kumar; Ravi Keswarwani; Atul Saini; Somnath Rudra (Urban Climate, 2024)

Data processing of visible emission line coronagraph onboard ADITYA-L1 - Muthu Priyal; Jagdev Singh; B. Raghavendra Prasad; Chavali Sumana; Varun Kumar; Shalabh Mishra; S.N. Venkata; G. Sindhuja; K. Sasikumar Raja; Amit Kumar; Sanal krishnan; Bhavana S. Hegde; et al. (Advances in Space Research, 2024)

Phenylalanine encapsulation into an amphiphilic carboxymethyl cellulose-derivative enhanced plant uptake and metabolism efficiency - Varun Kumar; Stalin Nadarajan; Anita Kumari; Yael Cohen; Tal Klingbel; Einat Bar; Efraim Lewinsohn; Yigal Elad; Elena Poverenov; Michal Oren-Shamir (Postharvest Biology and Technology, 2024)

Overexpression of the chickpea Metallothionein 1 (MT1) gene enhances drought tolerance in mustard (Brassica juncea L.) - Swati Lal; Varun Kumar; Uma Gupta; Sushma; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Unveiling predictive insights for enhanced performance of PVDF-based nanogenerators via machine learning modeling - S. Varun; Akash M. Chandran; K.P. Minhaj; Vishnu Shaju; Lity Alen Varghese; Prasanna Kumar S. Mural (Chemical Engineering Journal, 2024)

Overexpressing the glutaredoxin (CaGrx) gene enhances the antioxidant defences and improves drought tolerance in chickpea (Cicer arietinum L.) - Varun Kumar; Anil Kumar; Meenakshi; Uma Gupta; Shiv Narayan; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Chrysanthemum wilt caused by Fusarium incarnatum: Etiology unveiled through polyphasic taxonomic methods - Alexander Balamurugan; Mushineni Ashajyothi; Kumar Shanu; Krishnappa Charishma; Hiremath Varun; Kumar Gunjeet; Aundy Kumar (Physiological and Molecular Plant Pathology, 2024)

Physiological alterations and heavy metal accumulation in the transplanted lichen Pyxine cocoes (Sw.) Nyl. in Lucknow city, Uttar Pradesh - Kirti Kumari; Varun Kumar; Sanjeeva Nayaka; Gauri Saxena; Indraneel Sanyal (Environmental Monitoring and Assessment, 2024)

Detection and quantification of TIMP1 and miR-141 through RT-LAMP and TT-LAMP in serum samples during estrous cycle in buffalo - Mansi Joshi; Rajeev Chandel; Varun Kumar; Sanjay Sharma; Rubina Kumari Baithalu; Dheer Singh; Suneel Kumar Onteru (Reproductive Biology, 2023)

Highly sensitive detection of hazardous hydroquinone and chloramphenicol in the presence of paracetamol using cobalt tungstate (CoWO4) nanoplates modified electrode - Varun Pratap Singh; Gajendar Singh; Rajendra Patel; Umesh Kumar Gaur; Manu Sharma (Journal of Environmental Chemical Engineering, 2023)

Spatio-temporal variability analysis of evapotranspiration, water use efficiency and net primary productivity in the semi-arid region of Aravalli and Siwalik range, India - Shubham Kumar; Ritesh Kumar; Manoj Kumar; Alok Kumar Pandey; Prashant K. Srivastava; Sanchit Kumar; Varun Narayan Mishra; V. S. Arya (Environment, Development and Sustainability, 2023)

Comparative transcriptomic analysis of the chickpea glutaredoxin (CaGrx) gene over-expressed in Arabidopsis thaliana is associated with drought tolerance by modulating the plant defense system - Anil Kumar; Nasreen Bano; Mohd Akram Ansari; Varun Kumar; Sumit K. Bag; Indraneel Sanyal (Acta Physiologiae Plantarum, 2023)

Prognostic Potential of Thrombocyte Indices, Acute Phase Proteins, Electrolytes and Acid-Base Markers in Canine Parvovirus Infected Dogs With Systemic Inflammatory Response Syndrome - Babul Rudra Paul; Ujjwal Kumar De; Varun Kumar Sarkar; Jitendra Singh Gandhar; Manas Kumar Patra; Mithilesh Kumar Singh; Srishti Soni; Chethan Gollahalli Eregowda (Topics in Companion Animal Medicine, 2023)

Sustainability assessment framework of biomedical scaffolds: Additive manufacturing versus traditional manufacturing - Neha Choudhary; Varun Sharma; Pradeep Kumar (Journal of Cleaner Production, 2023)

Action of nanoparticles in the amelioration of heavy metal phytotoxicity - Afsana Praveen; Shilpy Singh; Varun Kumar Sharma (Cereal Research Communications, 2023)

Thermo-hydraulic performance of solar air heater having discrete D-shaped ribs as artificial roughness - Nitesh Dutt; Ankush Jageshwar Hedau; Ashwani Kumar; Mukesh Kumar Awasthi; Varun Pratap Singh; Gaurav Dwivedi (Environmental Science and Pollution Research, 2023)

Gangotri glacier dynamics from multi-sensor SAR and optical data - Praveen Kumar Thakur; Anukesh Krishnankutty Ambika; Sanjay M. Bisht; Alfred Stein; Anirudha Mahagaonkar; Uday Kumar; Vaibhav Garg; Varun Khajuria; Arpit Chouksey; Snehmani; Prakash Chauhan; SP Aggarwal (Advances in Space Research, 2023)

Freely Available Datasets Able to Simulate the Snowmelt Runoff in Himalayan Basin with the Aid of Temperature Index Modelling - Asha Thapliyal; Varun Khajuria; Praveen Kumar Thakur; Sanjeev Kimothi; Mahendra Pratap Singh Bisht; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2023)

Effect of Metal-resistant PGPB on the Metal Uptake, Antioxidative Defense, Physiology, and Growth of Atriplex lentiformis (Torr.) S.Wats. in Soil Contaminated with Cadmium and Nickel - Harsh Kumar; Shumailah Ishtiyaq; Paulo J. C. Favas; Mayank Varun; Manoj S. Paul (Journal of Plant Growth Regulation, 2023)

Quantitative analysis of human hairs and nails - Varun Bali; Yugal Khajuria; Vidit Maniyar; Pradeep K. Rai; Upendra Kumar; Charles Ghany; M.A. Gondal; Vivek K. Singh (Biophysical Reviews, 2023)

Growth studies in commercial broiler birds offered citric acid in formulated feed with low mineral density - Shivani Katoch; Sumani Sharma; Varun Sankhyan; Daisy Wadhwa; Arun Sharma; Sanjiv Kumar (Tropical Animal Health and Production, 2023)

Early-Life Intervention of Lactoferrin and Probiotic in Suckling Piglets: Effects on Immunoglobulins, Intestinal Integrity, and Neonatal Mortality - Varun Kumar Sarkar; Ujjwal Kumar De; Anju Kala; Ashok Kumar Verma; Anuj Chauhan; Babul Rudra Paul; Srishti Soni; Jitendra Singh Gandhar; Pallab Chaudhuri; Manas Kumar Patra; Chethan Gollahalli Eregowda; Gyanendra Kumar Gaur (Probiotics and Antimicrobial Proteins, 2023)

Metformin and Dapagliflozin Attenuate Doxorubicin-Induced Acute Cardiotoxicity in Wistar Rats: An Electrocardiographic, Biochemical, and Histopathological Approach - Shakta Mani Satyam; Laxminarayana Kurady Bairy; Prakashchandra Shetty; P. Sainath; Sanjay Bharati; Akheruz Zaman Ahmed; Varun Kumar Singh; A. J. Ashwal (Cardiovascular Toxicology, 2023)
Doxorubicin is a widely used anticancer drug whose efficacy is limited due to its cardiotoxicity. There is no ideal cardioprotection available against doxorubicin-induced cardiotoxicity. This study aimed to investigate the anticipated cardioprotective potential of metformin and dapagliflozin against doxorubicin-induced acute cardiotoxicity in Wistar rats. At the beginning of the experiment, cardiac screening of experimental animals was done by recording an electrocardiogram (ECG) before allocating them into the groups. Thereafter, a total of thirty healthy adult Wistar rats (150–200 g) were randomly divided into five groups ( n = 6) and treated for eight days as follows: group I (normal control), group II (doxorubicin control), group III (metformin 250 mg/kg/day), group IV (metformin 180 mg/kg/day), and group V (dapagliflozin 0.9 mg/kg/day). On the 7th day of the treatment phase, doxorubicin 20 mg/kg was administered intraperitoneal to groups II, III, IV, and V. On the 9th day (immediately after 48 h of doxorubicin administration), blood was collected from anesthetized animals for glucose, lipid profile, CK-MB & AST estimation, and ECG was recorded. Later, animals were sacrificed, and the heart was dissected for histopathological examination. We found that compared to normal control rats, CK-MB, AST, and glucose were significantly increased in doxorubicin control rats. There was a significant reversal of doxorubicin-induced hyperglycemia in the rats treated with metformin 250 mg/kg compared to doxorubicin control rats. Both metformin (180 mg/kg and 250 mg/kg) and dapagliflozin (0.9 mg/kg) significantly altered doxorubicin-induced ECG changes and reduced the levels of cardiac injury biomarkers CK-MB and AST compared to doxorubicin control rats. Metformin and dapagliflozin protected the cellular architecture of the myocardium from doxorubicin-induced myocardial injury. Current study revealed that both metformin and dapagliflozin at the FDA-recommended antidiabetic doses mitigated doxorubicin-induced acute cardiotoxicity in Wistar rats. The obtained data have opened the perspective to perform chronic studies and then to clinical studies to precisely consider metformin and dapagliflozin as potential chemoprotection in the combination of chemotherapy with doxorubicin to limit its cardiotoxicity, especially in patients with comorbid conditions like type II diabetes mellitus.

Multifaceted PVDF nanofibers in energy, water and sensors: A contemporary review (2018 to 2022) and future perspective - S. Varun; Nitish Manu George; Akash M. Chandran; Lity Alen Varghese; Prasanna Kumar S. Mural (Journal of Fluorine Chemistry, 2023)

A novel design for solar collector used for water heating application having nanofluid as working medium: CFD modeling and simulation - Rajneesh Kumar; Manjeet Kharub; Rajesh Sharma; Periapattana Nagaraj Hrisheekesha; Varun Goel; Suvanjan Bhattacharyya; Vineet Veer Tyagi; Varun (Environmental Science and Pollution Research, 2023)

Emergent properties of coupled bistable switches - Kishore Hari; Pradyumna Harlapur; Aditi Gopalan; Varun Ullanat; Atchuta Srinivas Duddu; Mohit Kumar Jolly (Journal of Biosciences, 2022)

Performance Evaluation of Google Earth Engine Based Precipitation Datasets Under Different Climatic Zones over India - Sukant Jain; Varun Tiwari; Amrit Thapa; Rohit Mangla; R. K. Jaiswal; Vinay Kumar; Supriya Tiwari; Mirela G. Tulbure; Ravi Galkate; A. K. Lohani; Kamal Pandey (Remote Sensing in Earth Systems Sciences, 2022)

Correction to: Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

Spatio-temporal variability and trend analysis of rainfall in Wainganga river basin, Central India, and forecasting using state-space models - Nanabhau S. Kudnar; Pranaya Diwate; Varun Narayan Mishra; Prashant K. Srivastava; Akshay Kumar; Manish Pandey (Theoretical and Applied Climatology, 2022)

A questionnaire-based survey of acceptability and satisfaction of virtual neurology clinic during COVID-19 lockdown: a preliminary study - Anand Kumar; Neha Lall; Abhishek Pathak; Deepika Joshi; Vijaya Nath Mishra; Rameshwar Nath Chaurasia; Varun Kumar Singh (Acta Neurologica Belgica, 2022)

Assessment of Different Spectral Unmixing Techniques on Space Borne Hyperspectral Imagery - Vinay Kumar; Kamal Pandey; Chinmaya Panda; Varun Tiwari; Shefali Agrawal (Remote Sensing in Earth Systems Sciences, 2022)

CAMTA transcription factor enhances salinity and drought tolerance in chickpea (Cicer arietinum L.) - Meenakshi; Anil Kumar; Varun Kumar; Arvind Kumar Dubey; Shiv Narayan; Samir V. Sawant; Veena Pande; Pramod Arvind Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Hypocholesterolemic Effect of Potent Peptide and Bioactive Fraction from Pigeon Pea By-Products in Wistar Rats - Varun Kumar; S. P. Muthu Kumar; Purnima Kaul Tiku (International Journal of Peptide Research and Therapeutics, 2021)

Effects of piperazine and EDTA in garden snail towards electrolytic variation and antimicrobial activities - Anil Kumar; Varun Dhiman; Pawan Kumar; Deepak Pant (Environmental Science and Pollution Research, 2021)

Developing an effectiveness index for biomedical waste management in Indian states using a composite indicators approach - Anurag Deepak; Dinesh Kumar; Varun Sharma (Environmental Science and Pollution Research, 2021)

Crop Health Assessment Using Sentinel-1 SAR Time Series Data in a Part of Central India - Sandeep Kumar Kaushik; Varun Narayan Mishra; Milap Punia; Pranaya Diwate; Thota Sivasankar; Anil Kumar Soni (Remote Sensing in Earth Systems Sciences, 2021)

Chia Seed Oil Ameliorates Doxorubicin-Induced Cardiotoxicity in Female Wistar Rats: An Electrocardiographic, Biochemical and Histopathological Approach - Akheruz Zaman Ahmed; Kamalesh D. Mumbrekar; Shakta Mani Satyam; Prakashchandra Shetty; Melanie Rose D’Souza; Varun Kumar Singh (Cardiovascular Toxicology, 2021)
Doxorubicin (DOX) is a potent anti-cancer antibiotic that was widely used for treatment of various cancers. It produces free radicals which result in extreme dose-limiting cardiotoxicity. This study investigated the cardioprotective potential of chia seed oil, an active polyphenolic nutraceutical against doxorubicin-induced cardiotoxicity in Wistar rats. Twenty-four female Wistar rats were divided into four groups ( n = 6) which consist of normal control, DOX control, test-A and test-B group. Animals were prophylactically treated with two different doses of test drug, i.e. chia seed oil 2.5 ml/kg/day and 5 ml/kg/day in test-A and test-B groups orally for 7 days. Doxorubicin (25 mg/kg; single dose) was administered intraperitoneally to DOX control, Test-A and Test-B animals on the seventh day to induce cardiotoxicity. ECG analysis was done before and after treatment. Besides ECG, CK, CK-MB, LDH, AST, MDA and GSH were analyzed. DOX had significantly altered ECG, CK, CK-MB, LDH, AST, MDA and GSH. Pre-treatment with chia seed oil significantly alleviated DOX-induced ECG changes and also guarded against DOX-induced rise of serum CK, CK-MB and AST levels. Chia seed oil alleviated histopathological alteration in DOX-treated rats. It also significantly inhibited DOX-induced GSH depletion and elevation of MDA. The present study revealed that chia seed oil exerts cardioprotection against doxorubicin-induced cardiotoxicity in female Wistar rats. Our study opens the perspective to clinical studies to precisely consider chia seed oil as a potential chemoprotectant nutraceutical in the combination chemotherapy with doxorubicin to limit its cardiotoxicity.

Fluoride-Induced Expression of Neuroinflammatory Markers and Neurophysiological Regulation in the Brain of Wistar Rat Model - Yugandhar P. Reddy; Santosh Tiwari; Lomas K. Tomar; Nalini Desai; Varun Kumar Sharma (Biological Trace Element Research, 2021)

A Cholesterol Homeostasis by Bioactive Peptide Fraction from Pigeon Pea By-Product: An In-Vitro Study - Varun Kumar; Purnima Kaul Tiku (International Journal of Peptide Research and Therapeutics, 2021)

Chickpea glutaredoxin (CaGrx) gene mitigates drought and salinity stress by modulating the physiological performance and antioxidant defense mechanisms - Anil Kumar; Varun Kumar; Arvind Kumar Dubey; Mohd Akram Ansari; Shiv Narayan; Meenakshi; Sanoj Kumar; Vivek Pandey; Veena Pande; Indraneel Sanyal (Physiology and Molecular Biology of Plants, 2021)

Geographically Weighted Method Integrated with Logistic Regression for Analyzing Spatially Varying Accuracy Measures of Remote Sensing Image Classification - Varun Narayan Mishra; Vivek Kumar; Rajendra Prasad; Milap Punia (Journal of the Indian Society of Remote Sensing, 2021)

The Modulatory Effect of Cholesterol Synthesis by Oryza sativa Derived Bioactive Peptide Fractions: An In Vitro Investigation - Varun Kumar; Lakshmy V. Kurup; Purnima Kaul Tiku (International Journal of Peptide Research and Therapeutics, 2021)

Recovery of nanosized silica and lignin from sugarcane bagasse waste and their engineering in fabrication of composite membrane for water purification - Baljinder Singh Kauldhar; Balwinder Singh Sooch; Shushil Kumar Rai; Varun Kumar; Sudesh Kumar Yadav (Environmental Science and Pollution Research, 2021)

Bioprospecting potential of microbial communities in solid waste landfills for novel enzymes through metagenomic approach - Karnika Thakur; Manisha Chownk; Varun Kumar; Anjali Purohit; Alokika Vashisht; Vinod Kumar; Sudesh Kumar Yadav (World Journal of Microbiology and Biotechnology, 2020)

A study of comorbidities in myasthenia gravis - Usha K. Misra; Jayantee Kalita; Varun K. Singh; Surendra Kumar (Acta Neurologica Belgica, 2020)

Women as Drivers of Change for Nutrition-Sensitive Agriculture: Case Study of a Novel Extension Approach in Wardha, India - R Rukmani; R. Gopinath; G. Anuradha; R. Sanjeev; Varun Kumar Yadav (Agricultural Research, 2019)

Genetic variant rs10937405 of TP63 and susceptibility to lung cancer risk in north Indian population - GH. Rasool Bhat; Amrita Bhat; Sonali Verma; Itty Sethi; Ruchi Shah; Varun Sharma; S. Minerva; Divya Bakshi; Bhanu Sharma; Sandeep Koul; Deepak Abrol; Audesh Bhat; et al. (Journal of Genetics, 2019)

Evaluation of anti-dengue activity of Carica papaya aqueous leaf extract and its role in platelet augmentation - Navita Sharma; Kamla Prasad Mishra; Sudipta Chanda; Varun Bhardwaj; Himanshi Tanwar; Lilly Ganju; Bhuvnesh Kumar; Shashi Bala Singh (Archives of Virology, 2019)

Polyglutamic Acid Functionalization of Chitosan Nanoparticles Enhances the Therapeutic Efficacy of Insulin Following Oral Administration - Dileep Urimi; Ashish Kumar Agrawal; Varun Kushwah; Sanyog Jain (AAPS PharmSciTech, 2019)

Performance evaluation of textural features in improving land use/land cover classification accuracy of heterogeneous landscape using multi-sensor remote sensing data - Varun Narayan Mishra; Rajendra Prasad; Praveen Kumar Rai; Ajeet Kumar Vishwakarma; Aman Arora (Earth Science Informatics, 2019)

Oral Delivery of Methylthioadenosine to the Brain Employing Solid Lipid Nanoparticles: Pharmacokinetic, Behavioral, and Histopathological Evidences - Pramod Kumar; Gajanand Sharma; Varun Gupta; Ramanpreet Kaur; Kanika Thakur; Ruchi Malik; Anil Kumar; Naveen Kaushal; Om Prakash Katare; Kaisar Raza (AAPS PharmSciTech, 2019)

Atmospheric abundance of HULIS during wintertime in Indo-Gangetic Plain: impact of biomass burning emissions - Varun Kumar; Prashant Rajput; Anubha Goel (Journal of Atmospheric Chemistry, 2018)

Amphotericin B Loaded Chitosan Nanoparticles: Implication of Bile Salt Stabilization on Gastrointestinal Stability, Permeability and Oral Bioavailability - Sanyog Jain; Chamala Siva Kumar Reddy; Rajan Swami; Varun Kushwah (AAPS PharmSciTech, 2018)

Prediction of spatio-temporal land use/land cover dynamics in rapidly developing Varanasi district of Uttar Pradesh, India, using geospatial approach: a comparison of hybrid models - Varun Narayan Mishra; Praveen Kumar Rai; Rajendra Prasad; Milap Punia; Mărgărit-Mircea Nistor (Applied Geomatics, 2018)

Ground Based Bistatic Scatterometer Measurement for the Estimation of Growth Variables of Ladyfinger Crop at X-Band - Ajeet Kumar Vishwakarma; Rajendra Prasad; Dileep Kumar Gupta; Pradeep Kumar; Varun Narayan Mishra (Journal of the Indian Society of Remote Sensing, 2018)

Lyotropic Liquid Crystalline Nanoparticles of Amphotericin B: Implication of Phytantriol and Glyceryl Monooleate on Bioavailability Enhancement - Sanyog Jain; Pooja Yadav; Rajan Swami; Nitin Kumar Swarnakar; Varun Kushwah; Sameer S. Katiyar (AAPS PharmSciTech, 2018)

Studies on biogas-fuelled compression ignition engine under dual fuel mode - Sunil Kumar Mahla; Varun Singla; Sarbjot Singh Sandhu; Amit Dhir (Environmental Science and Pollution Research, 2018)

Reconstructing the demographic history of the Himalayan and adjoining populations - Rakesh Tamang; Gyaneshwer Chaubey; Amrita Nandan; Periyasamy Govindaraj; Vipin Kumar Singh; Niraj Rai; Chandana Basu Mallick; Vishwas Sharma; Varun Kumar Sharma; Anish M. Shah; Albert Lalremruata; Alla G. Reddy; et al. (Human Genetics, 2018)

Neuroleptic malignant syndrome as a presenting feature of subacute sclerosing panencephalitis - Divyani Garg; Varun Reddy; Rajesh Kumar Singh; Deepa Dash; Rohit Bhatia; Manjari Tripathi (Journal of NeuroVirology, 2018)

Novel Gemcitabine Conjugated Albumin Nanoparticles: a Potential Strategy to Enhance Drug Efficacy in Pancreatic Cancer Treatment - Varun Kushwah; Ashish Kumar Agrawal; Chander Parkash Dora; David Mallinson; Dimitrios A. Lamprou; Ramesh C. Gupta; Sanyog Jain (Pharmaceutical Research, 2017)

Stable Co-crystals of Glipizide with Enhanced Dissolution Profiles: Preparation and Characterization - Narendra Kumar Pandey; Hans Raj Sehal; Varun Garg; Tejasvi Gaur; Bimlesh Kumar; Sachin Kumar Singh; Monica Gulati; K. Gowthamarajan; Palak Bawa; Sarvi Yadav Rajesh; Parth Sharma; Rakesh Narang (AAPS PharmSciTech, 2017)

Leopard–Human Conflict Led Casualties and Conservation Awareness Campaign in Shivalik Hills of Northern India - Pradeep Kumar; Sangeeta Chandel; Vijay Kumar; Varun Sankhyan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Improved Stability and Enhanced Oral Bioavailability of Atorvastatin Loaded Stearic Acid Modified Gelatin Nanoparticles - Deepanshu Shilpi; Varun Kushwah; Ashish Kumar Agrawal; Sanyog Jain (Pharmaceutical Research, 2017)

Comparative Study of Two ELISA Kits for Estimation of Antibodies to Hepatitis B Virus in Human Normal Immunoglobulin and Specific Immunoglobulin Intended for Intravenous or Intramuscular Use - J. P. Prasad; Y. Madhu; Arushi Mandhan; Payal Garg; Anu Prakash; Varsha Singh; Daud Ali; Prdeep Kumar; Surinder Singh; G. R. Soni; Varun Singh (Indian Journal of Clinical Biochemistry, 2017)

Comparative whole-transcriptome analysis in Podophyllum species identifies key transcription factors contributing to biosynthesis of podophyllotoxin in P. hexandrum - Pawan Kumar; Varun Jaiswal; Tarun Pal; Jagdish Singh; Rajinder S. Chauhan (Protoplasma, 2017)

Biosynthesis and therapeutic implications of iridoid glycosides from Picrorhiza genus: the road ahead - Varun Kumar; Rajinder Singh Chauhan; Chanderdeep Tandon (Journal of Plant Biochemistry and Biotechnology, 2017)

Systematic Development of Transethosomal Gel System of Piroxicam: Formulation Optimization, In Vitro Evaluation, and Ex Vivo Assessment - Varun Garg; Harmanpreet Singh; Amit Bhatia; Kaisar Raza; Sachin Kumar Singh; Bhupinder Singh; Sarwar Beg (AAPS PharmSciTech, 2017)

Modulation of Picroside-I Biosynthesis in Grown Elicited Shoots of Picrorhiza kurroa In Vitro - Neha Sharma; Varun Kumar; Rajinder Singh Chauhan; Hemant Sood (Journal of Plant Growth Regulation, 2016)

Higher amount of steviol detected in the leaves of a non-toxic endangered medicinal herb, Aconitum heterophyllum - Varun Kumar; Rajinder Singh Chauhan (Journal of Plant Biochemistry and Biotechnology, 2016)

Anticancer activity of Ophiobolin A, isolated from the endophytic fungus Bipolaris setariae - Dimple R. Bhatia; Payal Dhar; Varun Mutalik; Sunil Kumar Deshmukh; Shilpa A. Verekar; Dattatraya C. Desai; Rajendra Kshirsagar; Padma Thiagarajan; Veena Agarwal (Natural Product Research, 2016)

Optimization of a preparative RP-HPLC method for isolation and purification of picrosides in Picrorhiza kurroa - Varun Kumar; Hemant Sood; Rajinder Singh Chauhan (Journal of Plant Biochemistry and Biotechnology, 2016)

Tracking dynamics of enzyme activities and their gene expression in Picrorhiza kurroa with respect to picroside accumulation - Varun Kumar; Kirti Shitiz; Rajinder Singh Chauhan; Hemant Sood; Chanderdeep Tandon (Journal of Plant Biochemistry and Biotechnology, 2016)

A remote sensing aided multi-layer perceptron-Markov chain analysis for land use and land cover change prediction in Patna district (Bihar), India - Varun Narayan Mishra; Praveen Kumar Rai (Arabian Journal of Geosciences, 2016)

An insight into conflux of metabolic traffic leading to picroside-I biosynthesis by tracking molecular time course changes in a medicinal herb, Picrorhiza kurroa - Varun Kumar; Neha Sharma; Kirti Shitiz; Tiratha Raj Singh; Chanderdeep Tandon; Hemant Sood; Rajinder Singh Chauhan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Cost effective quantification of picrosides in Picrorhiza kurroa by employing response surface methodology using HPLC-UV - Varun Kumar; Varun Kumar; Rajinder Singh Chauhan; Hemant Sood; Chanderdeep Tandon (Journal of Plant Biochemistry and Biotechnology, 2015)

Expression analysis of biosynthetic pathway genes vis-à-vis podophyllotoxin content in Podophyllum hexandrum Royle - Pawan Kumar; Tarun Pal; Neha Sharma; Varun Kumar; Hemant Sood; Rajinder S. Chauhan (Protoplasma, 2015)

Detection of intermediates through high-resolution mass spectrometry for constructing biosynthetic pathways for major chemical constituents in a medicinally important herb, Swertia chirayita - Varun Kumar; Hemant Sood; Rajinder Singh Chauhan (Natural Product Research, 2015)

Abutilon indicum L.: a prospective weed for phytoremediation - Mayank Varun; Disha Jaggi; Rohan D’Souza; Manoj S. Paul; Bhumesh Kumar (Environmental Monitoring and Assessment, 2015)

Hydrogen sulfide mitigates homocysteine-mediated pathological remodeling by inducing miR-133a in cardiomyocytes - Varun Kesherwani; Shyam Sundar Nandi; Surender K. Sharawat; Hamid R. Shahshahan; Paras Kumar Mishra (Molecular and Cellular Biochemistry, 2015)

Influence of gamma rays and ethyl methane sulphonate (EMS) on the levels of phytic acid, raffinose family oligosaccharides and antioxidants in soybean seeds of different genotypes - Awadhesh Kumar; Varun Kumar; S. K. Lal; Monica Jolly; Archana Sachdev (Journal of Plant Biochemistry and Biotechnology, 2015)

Comparison of support vector machine, artificial neural network, and spectral angle mapper algorithms for crop classification using LISS IV data - Pradeep Kumar; Dileep Kumar Gupta; Varun Narayan Mishra; Rajendra Prasad (International Journal of Remote Sensing, 2015)

Quantitative structure–activity relationship (QSAR) studies as strategic approach in drug discovery - Harun M. Patel; Malleshappa N. Noolvi; Poonam Sharma; Varun Jaiswal; Sumit Bansal; Sandeep Lohan; Suthar Sharad Kumar; Vikrant Abbot; Saurabh Dhiman; Varun Bhardwaj (Medicinal Chemistry Research, 2014)

Rainfall variability and indices of extreme rainfall-analysis and perception study for two stations over Central Himalaya, India - Sneh Joshi; Kireet Kumar; Varun Joshi; Bimal Pande (Natural Hazards, 2014)

The first multituberculate mammal from India - Varun Parmar; Guntupalli V. R. Prasad; Deepak Kumar (The Science of Nature, 2013)

Antifertility activity of methanolic bark extract of Aegle marmelos (l.) in male wistar rats - Shyam S Agrawal; Ashok Kumar; Sumeet Gullaiya; Vishal Dubey; Ashish Nagar; Poonam Tiwari; Parul Dhar; Varun Singh (DARU Journal of Pharmaceutical Sciences, 2012)

Effects of salicylic acid on seedling growth and nitrogen use efficiency in cucumber ( Cucumis sativus L.) - Pramod Kumar Singh; Varun Kumar Chaturvedi (Plant Biosystems, 2012)

Bioassay as monitoring system for lead phytoremediation through Crinum asiaticum L. - Mayank Varun; Rohan D’Souza; Devendra Kumar; Manoj S. Paul (Environmental Monitoring and Assessment, 2011)

Relevance of Helicobacter pylori genotypes in gastric pathology and its association with plasma malondialdehyde and nitric oxide levels - Santosh K. Tiwari; G. Manoj; Vishwas Sharma; G. Sivaram; R. Saikant; Avinash Bardia; Varun K. Sharma; Zakia Abid; Aleem A. Khan; M. Aejaz Habeeb; C. M. Habibullah; B. Santhosh Kumar; et al. (Inflammopharmacology, 2010)

Immunomodulator Effect of Picroliv and its Potential in Treatment Against Resistant Plasmodium yoelii (MDR) Infection in Mice - Varun Dwivedi; Arif Khan; Azevedo Vasco; Nishat Fatima; Vishal Kumar Soni; Anil Dangi; Shailja Misra-Bhattacharya; Mohammad Owais (Pharmaceutical Research, 2008)